4p-2(2-3p)=6(p-6)-36

Simple and best practice solution for 4p-2(2-3p)=6(p-6)-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4p-2(2-3p)=6(p-6)-36 equation:


Simplifying
4p + -2(2 + -3p) = 6(p + -6) + -36
4p + (2 * -2 + -3p * -2) = 6(p + -6) + -36
4p + (-4 + 6p) = 6(p + -6) + -36

Reorder the terms:
-4 + 4p + 6p = 6(p + -6) + -36

Combine like terms: 4p + 6p = 10p
-4 + 10p = 6(p + -6) + -36

Reorder the terms:
-4 + 10p = 6(-6 + p) + -36
-4 + 10p = (-6 * 6 + p * 6) + -36
-4 + 10p = (-36 + 6p) + -36

Reorder the terms:
-4 + 10p = -36 + -36 + 6p

Combine like terms: -36 + -36 = -72
-4 + 10p = -72 + 6p

Solving
-4 + 10p = -72 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
-4 + 10p + -6p = -72 + 6p + -6p

Combine like terms: 10p + -6p = 4p
-4 + 4p = -72 + 6p + -6p

Combine like terms: 6p + -6p = 0
-4 + 4p = -72 + 0
-4 + 4p = -72

Add '4' to each side of the equation.
-4 + 4 + 4p = -72 + 4

Combine like terms: -4 + 4 = 0
0 + 4p = -72 + 4
4p = -72 + 4

Combine like terms: -72 + 4 = -68
4p = -68

Divide each side by '4'.
p = -17

Simplifying
p = -17

See similar equations:

| -[8z-(14z+1)]=1+(5z+0) | | 0=x^2-4.75x+3 | | 10x^2+5-7x-6x^2-13x= | | 2*(4x-3)=3x-5 | | x^2-4.75-24=0 | | 6(x-6)-8(x+2)=-10 | | 6x-15=9+3x | | 13x+17y=19 | | 2x+10=6+4x | | -7(x+4)+4x+7=8x+6 | | 7/60=a | | 2x-16=-128 | | 1.4(x)=2x-3 | | 2/5*7/-6*-7=a | | .5(x)=2x-3 | | x+18=106 | | 2/5*7/-6*-7 | | -1(x)=2x-3 | | 1(x)=2x-3 | | 4/-6+2=-1 | | 3(x)=2x-3 | | 3(6x-4)-4(x+7)=6x-96+x | | 4(4x+1)=3x-4(6-x)8 | | 2.75(x)=2x-3 | | -7(x-2)=-4 | | 0.86=exp(-6.2831*f) | | 0.86=exp(-2*pi*f) | | (3x-2)2=(2x+3)2 | | 9^4x*27^2-3x=1/9 | | x^5x^7/x^6 | | 5-2q=3Q | | 6(4+2x)-(8x-22)=68 |

Equations solver categories